Rancang Bangun Alat Peraga Water Heater Menggunakan Heater Portable Dan Sensor Ds18b20 Berbasis Arduino Uno R3 Pada Konsep Termodinamika - Alfiatun Hasanah; Cindy Ferdianty; Lia Silvira; Naili Farika; Nurul Faradillah; Alex Harijanto; Subiki S (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to enable high school/MA students 1) to know and design a Water Heater Demonstration Tool Using an Arduino Uno R3-Based Portable Heater and a DS18B20 Sensor on the Thermodynamics Concept, 2) to know the results of experiments using an Arduino Uno-based Water Heater trainer on the Thermodynamics concept , 3) can find out the comparison of the results of the Arduino-based demonstration with the display shown by the Thermodynamics temperature measuring device. This research method uses the Research and Development method. The results of the study show that the weather heater trainer using the Arduino-based portable heater and sensor DS18B20 can explain the concept of thermodynamics in the discussion of energy changes, heat insulation against temperature properly. This teaching aid obtains measurement results with the smallest error value of -3.95% and the largest error of 2.27% when compared to the results of measuring the temperature of the thermometer.